وصف الحافظ ابن رجب الأحاديث في البخاري بأنها ليست على شرط مسلم مما فيه اختلاف في فتح الباري "دراسة نقدية عللية": Al-Ḥāfiẓ Ibn Rajab's View on Hadiths in Sahih Bukhari That do Not Meet Muslim's Conditions, as Discussed in Fatḥ Al-Bārī (a Critical Study of Al-‘Ilal) - Muhammad Isa Abdullah (البصيرة: مجلة الدراسات الإسلامية, 2024)
This study examines the marfu' hadiths or those that are indicated as not being classified as authentic (sahih) by Imam Muslim. Al-Hafiz Ibn Rajab stated or suggested that these hadiths do not meet the conditions set by Muslim in his book Fath al-Bari due to differing views. The aim of this research is to identify the hadiths that Al-Hafiz Ibn Rajab stated or indicated as not meeting Muslim’s conditions in his Fath al-Bari, analyze the differences in opinions, and draw conclusions based on the rulings of muhaddithun (hadith scholars) regarding which view is more accurate (rajih). Additionally, the study seeks to highlight the reasons why Al-Hafiz Ibn Rajab classified these hadiths as not adhering to Muslim’s criteria. Using inductive, analytical, and critical approaches, the researcher discovered several key findings. Seven hadiths in Fath al-Bari by Ibn Rajab were identified as being reported by Imam al-Bukhari but not fulfilling Muslim's conditions. Of these, five were selected for further examination, and the reasons why these hadiths did not meet Muslim’s standards were sought from the statements of Al-Hafiz Ibn Rajab. The researcher found that for each of these hadiths, there were two or more points of contention, such as differences in determining whether the hadith is marfu' or not, disagreements over whether the hadith is mauquf or not, or discrepancies in the chain of transmission (sanad), the text (matan), the names of the companions mentioned, or other factors.